2009
DOI: 10.1016/j.ijdevneu.2009.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Increased apoptosis and reduced neuronal and glial densities in the hippocampus due to nicotine and ethanol exposure in adolescent mice

Abstract: It has been recently shown that nicotine and ethanol interact during adolescence affecting memory/learning and anxiety levels. Considering the role of the hippocampus in both anxiety and memory/learning, we investigated whether adolescent nicotine and/or ethanol administration elicit apoptotic cell death and whether this results in neuronal and/or glial density alterations in the following regions of the hippocampus: granular layer of the dentate gyrus (GrDG), molecular layer (Mol), CA1, CA2 and CA3. From the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 100 publications
(161 reference statements)
1
27
1
Order By: Relevance
“…Although it is still controversial, the potential hazard of ASs has received much attention due to the carcinogenicity (Olney et al, 1996;Reuber, 1978;Weihrauch and Diehl, 2004) and brain damage (Oliveira-da-Silva et al, 2009) of saccharin and aspar tame, respectively. However, there have been no reports to determine the physiologic roles of ASs in serum lipoprotein metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is still controversial, the potential hazard of ASs has received much attention due to the carcinogenicity (Olney et al, 1996;Reuber, 1978;Weihrauch and Diehl, 2004) and brain damage (Oliveira-da-Silva et al, 2009) of saccharin and aspar tame, respectively. However, there have been no reports to determine the physiologic roles of ASs in serum lipoprotein metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Lead (Pb) is a common neurotoxicant, and it was found to induce apoptosis in the hippocampus of experimental animals in vivo 25) . Some studies have shown that other neurotoxicants such as CuO, MnCl 2 and ethanol also induced hippocampal neural apoptosis in rats or mice 20,24,26) . These studies indicate that the hippocampus may be a target organ of the neurotoxic agents.…”
mentioning
confidence: 99%
“…Indeed, a critical role for ethanol in promoting apoptotic events in various cell lines and animal models has been well documented. [20][21][22][23][24][25][26][27][28][29] Also, ethanol stimulates the TRAIL-induced apoptosis in leukemic T-lymphocytes and colon cancer cells in vitro. 38,39 Despite these data, an interactive effect of ethanol and TRAIL in promoting PCa cell death has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19] Ethanol-induced apoptotic cell death has been well recognized in many cell types and animal models. [20][21][22][23][24] High concentrations of ethanol can effectively destroy hepatoma tumor as well as normal cells, whereas lower concentrations of ethanol selectively induces apoptosis in hepatoma tumor cells but not in normal hepatocytes. 25 Ethanol induces significant apoptosis of purkinje cells in the developing cerebellum.…”
Section: Introductionmentioning
confidence: 99%